Isolation of Sulfate-Reducing Bacteria from Sediments Above the Deep-Subseafloor Aquifer - Fichtel, Katja; Mathes, Falko; Könneke, Martin; Cypionka, Heribert; Engelen, Bert (Frontiers in Microbiology, 2012)
On a global scale, crustal fluids fuel a substantial part of the deep subseafloor biosphere by providing electron acceptors for microbial respiration. In this study, we examined bacterial cultures from a sediment column of the Juan de Fuca Ridge, Northeast Pacific (IODP Site U1301) which is divided into three distinctive compartments: an upper sulfate-containing zone, formed by bottom-seawater diffusion, a sulfate-depleted zone and a second (~140 m thick) sulfate-containing zone influenced by fluid diffusion from the basaltic aquifer. Sulfate reducers were isolated from near-surface and near-basement sediments. All initial enrichments harboured specific communities of heterotrophic microorganisms. Among those, the number of isolated spore-forming Firmicutes decreased from 60% to 21% with sediment depth. Strains affiliated to Desulfosporosinus lacus, Desulfotomaculum sp. and Desulfovibrio aespoeensis were recovered from the upper sediment layers (1.3-9.1 meters below seafloor, mbsf). Several strains of Desulfovibrio indonesiensis and one relative of Desulfotignum balticum were isolated from near-basement sediments (240-262 mbsf). The physiological investigation of strains affiliated to D. aespoeensis, D. indonesiensis and D. balticum indicated that they were all able to use sulfate, thiosulfate and sulfite as electron acceptors. In the presence of sulfate, they grew strain-specifically on a few short-chain n-alcohols and fatty acids, only. The strains fermented either ethanol, pyruvate or betaine. Interestingly, all strains utilized hydrogen and the isolate affiliated to D. indonesiensis even exhibited an autotrophic life-mode. Thus, in the deep subseafloor where organic substrates are limited or hardly degradable, hydrogen might become an essential electron donor. The isolation of non-sporeforming sulfate reducers from fluid-influenced layers indicates that they have survived the long-term burial as active populations even after the separation from the seafloor.